Translation of Slang Variety in the movie Hard Feeling into Indonesian by Students - Aulia Syarifatul Husna; Rosyidah Rosyidah (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This research aims to classify the varieties of slang in the movie Hard Feeling based on Ehmann’s theory and describe the translation strategies used by students of Department of German Literature, State University of Malang in translating slang varieties in the movie based on Pedersen’s theory. This research uses descriptive method with qualitative approach. Words, phrases, and sentences belonging to the slang varieties contained in the subtitles of the movie and the translation results of students are the data in this research which were collected using Simak and Catat techniques and analyzed using Miles and Huberman data analysis technique. This research uses instruments, namely Human Instrument and documentation tables. The results of data analysis were validated using Murdiyanto’s technique, namely Meningkatkan Ketekunan. The result of data analysis shows that the 74 data of slang varieties in this movie are classified into Fremdsprache Anleihen, Bedeutungsumkehrung, Vereinfachung, Klangliche Eindeutschung, Wortneuschöpfung, Bedeutungserweiterung, Bedeutungsverengung, Bedeutungsverschiebung, and Kreative Wortspielen. In addition, the translation strategies used are Situational Substitution, Calque, Completed Unmarked Retention, Paraphrase, TL-Adjusted Retention, Generalization Superordinate Term, Omission, and Completion. Keywords: slang variety, translation strategy, film, student